Male-specific cardiac pathologies in mice lacking either the A or B subunit of factor XIII - Souri, Masayoshi; Koseki-Kuno, Shiori; Takeda, Naoki; Yamakawa, Mitsunori; Takeishi, Yasuchika; Degen, Jay L.; Ichinose, Akitada (Thrombosis and Haemostasis, 2008)
Factor XIII (FXIII) is a proenzyme of plasma transglutaminase consisting of enzymatic A subunits (FXIII-A) and non-catalytic B subunits (FXIII-B), and acts in haemostasis and wound healing. We generated mice lacking either FXIII-A or FXIII-B to investigate the physiological functions of FXIII in vivo. A longitudinal study was carried out using the gene-targeted mice to explore the possible effects of FXIII deficiency on aging. Survival rates of FXIII-A-/- males decreased to approximately 50% at 10 months after birth, although most FXIII-A-/- females and both genders of wild-type mice survived. Four FXIII-A-/- males died of severe intra-thoracic haemorrhage, and a large haematoma was found in their hearts. Haemorrhage, haemosiderin deposition and/or fibrosis were observed in the hearts of other dead FXIII-A-/- males. Fibrosis together with haemosiderin deposition was also found in the hearts of FXIII-A-/- males sacrificed. The in-vivo cardiac function was normal in FXIII-A-/- mice when compared with wild-type mice despite the presence of significant cardiac fibrosis. Although survival rates for both genders of the FXIII-B-/- and wild-type mice did not differ, mild fibrosis together with haemosiderin deposits were only found in the hearts of the sacrificed FXIII-B-/- males. Carditis and fibrosis in FXIII-deficient mice might be caused by a faulty or delayed reparative process that was initiated by abnormal haemorrhagic events within heart tissue. It is important therefore to examine possible cardiac involvement in human patients with congenital FXIII deficiency.
Keywords: Transglutaminase; haemostasis; wound healing; gene-targeting